Impact of Syndecan-2-Selected Mesenchymal Stromal Cells on the Early Onset of Diabetic Cardiomyopathy in Diabetic db/db Mice - Pappritz, Kathleen; Dong, Fengquan; Miteva, Kapka; Kovacs, Arpad; El-Shafeey, Muhammad; Kerim, Bahtiyar; O'Flynn, Lisa; Elliman, Stephen Joseph; O'Brien, Timothy; Hamdani, Nazha; Tschöpe, Carsten; Van Linthout, Sophie (Frontiers in Cardiovascular Medicine, 2021)
Background: Mesenchymal stromal cells (MSC) are an attractive cell-type for cell therapy given their immunomodulatory, anti-fibrotic, and endothelial-protective features. The heparin sulphate proteoglycan, syndecan-2/CD362, has been identified as a functional marker for MSC isolation, allowing one to obtain a homogeneous cell product that meets regulatory requirements for clinical use. We previously assessed the impact of wildtype (WT), CD362- and CD362+ MSC on local changes in protein distribution in left ventricle (LV) tissue and on LV function in an experimental model of early onset diabetic cardiomyopathy. The present study aimed to further explore their impact on mechanisms underlying diastolic dysfunction in this model. Materials: For this purpose, 1x106 WT, CD362-, or CD362+ MSC were intravenously (i.v.) injected into 20 week (w) old diabetic BKS.Cg-m+/+Leprdb/BomTac, i.e. db/db mice. Control animals (db+/db) were injected with the equivalent volume of PBS alone. After 4 w, mice were sacrificed for further analysis. Results: Treatment with all three MSC populations had no impact on blood glucose levels in db/db mice. WT, CD362-, and CD362+ MSC application restored LV nitric oxide (NO) and cyclic guanosine monophosphate (cGMP) levels in db/db mice, which correlated with a reduction in cardiomyocyte stiffness. Furthermore, all stromal cells were able to increase arteriole density in db/db mice. The effect of CD362+ MSC on NO and cGMP levels, cardiomyocyte stiffness and arteriole density was less pronounced than in mice treated with WT or CD362- MSC. Analysis of collagen I and III protein expression revealed that fibrosis had not yet developed at this stage of experimental diabetic cardiomyopathy. All MSC reduced the number of cardiac CD3+ and CD68+ cells in db/db mice, whereas only splenocytes from CD362– and CD362+-db/db mice exhibited a lower pro-fibrotic potential compared to splenocytes from db/db mice. Conclusion: CD362+ MSC application decreased cardiomyocyte stiffness, raised myocardial NO and cGMP levels, and increased arteriole density, although to a lesser extent than WT and CD362- MSC in an experimental model of early onset diabetic cardiomyopathy without cardiac fibrosis. These findings suggest that the degree in improvement of cardiomyocyte stiffness following CD362+ MSC application was insufficient to improve diastolic function.